Peer effects, social multipliers and migrants at school: an international comparison - Horst Entorf; Martina Lauk (Institute for the Study of Labor (IZA), 2006)
This article analyses the school performance of migrants dependent on peer groups in different international schooling environments. Using data from the international OECD PISA test, we consider social interaction within and between groups of natives and migrants. Results based on social multipliers (Glaeser et al. 2000, 2003) suggest that both native-to-native and migrant-to-migrant peer effects are higher in ability-differencing school systems than in comprehensive schools. Thus, non-comprehensive school systems seem to magnify the already existing educational inequality between students with a low parental socioeconomic migration background and children from more privileged families. Students with a migration background and a disadvantageous parental status would benefit from higher diversity within schools.
Keywords: I21; 330; peer effects; migration; education; social multipliers; school systems; parental socioeconomic background